2014
DOI: 10.3109/08990220.2014.937413
|View full text |Cite
|
Sign up to set email alerts
|

EMG activity of finger flexor muscles and grip force following low-dose transcutaneous electrical nerve stimulation in healthy adult subjects

Abstract: Somatosensory stimulation modulates cortical and corticospinal excitability and consequently affects motor output. Therefore, low-amplitude transcutaneous electrical nerve stimulation (TENS) has the potential to elicit favorable motor responses. The purpose of the two presented pilot studies was to shed light on TENS parameters that are relevant for the enhancement of two desirable motor outcomes, namely, electromyographic (EMG) activity and contraction strength of the finger flexors and wrist muscles. In 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Klaiput and Kitisomprayoonkul delivered low frequency stimulation (burst of alternating current at 1 Hz consisting of 5 pulses of 1‐millisecond duration, at 10 Hz, for 500 milliseconds with 50% duty cycle) over the median and ulnar nerves at the wrist in chronic and subacute stroke patients and reported increased pinch strength. Kafri et al reported that the effect of 150 Hz frequency TENS, applied to the skin overlying the finger flexor muscles, on EMG output was not significant, whereas low frequency bursts of TENS enhanced EMG activity and grip force. No previous study reported reduced of myoelectrical activity or hand muscle force post surface stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Klaiput and Kitisomprayoonkul delivered low frequency stimulation (burst of alternating current at 1 Hz consisting of 5 pulses of 1‐millisecond duration, at 10 Hz, for 500 milliseconds with 50% duty cycle) over the median and ulnar nerves at the wrist in chronic and subacute stroke patients and reported increased pinch strength. Kafri et al reported that the effect of 150 Hz frequency TENS, applied to the skin overlying the finger flexor muscles, on EMG output was not significant, whereas low frequency bursts of TENS enhanced EMG activity and grip force. No previous study reported reduced of myoelectrical activity or hand muscle force post surface stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Postural sway, or horizontal movement from the center of gravity, is another component of balance impairment, as it reflects the postural control system's ability to stabilize the moving center of mass. A large body of work has demonstrated age effects on sway, including age-related increases in sway amplitude [ 12 - 16 ]. While there are central factors that contribute to age-related changes in sway, peripheral effects such as sarcopenia, coupled with larger proportions of Type I and the loss of the more powerful Type II muscle fibers in older adults, is also important in the development of age-related sway patterns [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor tractography (DTT), derived from diffusion tensor imaging (DTI), enables three-dimensional reconstruction, and evaluation of the spinothalamic tract (STT). [6] Several studies using DTT have demonstrated that injury of the STT is a pathogenetic mechanism of central pain following TBI. [710] However, no study of headache due to injury of the STT has been reported.…”
Section: Introductionmentioning
confidence: 99%